Pattern of Visual Analog Score Changes in Metastatic Urogenital Cancer Patients Undergoing Sympathectomy - Dicky Panduwinata; Maximillian Ch Oley; Eko Prasetyo (International Journal of Health and Pharmaceutical (IJHP), 2024)
This study aimed to evaluate the effectiveness of sympathectomy in reducing pain in patients with metastatic urogenital cancer. A single-blind randomized clinical trial involving five patients who underwent neurolytic ganglion impar block using a transcoccygeal approach, followed by radiofrequency ablation (RFA), was conducted. Five patients with metastatic urogenital cancer, averaging 58.4 ± 16.9 years old, showed a significant reduction in pain after sympathectomy. The average Visual Analog Scale (VAS) reduction was 2 points on the first day, 4 points on the third day, and 5 points on the fifth day. This pain reduction was accompanied by a decrease in the patients' dependence on opioid medication. Sympathectomy and radiofrequency ablation have proven effective in reducing pain in patients with metastatic urogenital cancer. These findings support the use of sympathectomy as part of comprehensive pain management in metastatic cancer patients, improving quality of life and reducing opioid usage. This approach offers a promising alternative for managing chronic pain in this patient population, particularly when oral therapy is insufficient.